1979
DOI: 10.7164/antibiotics.32.874
|View full text |Cite
|
Sign up to set email alerts
|

Conglobatin, a novel macrolide dilactone from Streptomyces conglobatus ATCC 31005.

Abstract: Fermentationof deposited cultures of Streptomyces conglobatus, known to produce the polyether antibiotic, ionomycin has resulted in the isolation and characterization of a second metabolite, conglobatin (C28H33N2O6). X-Ray analysis revealed a dimeric macrolide dilactone structure for conglobatin, similar to the structures of the mold metabolites vermiculin and pyrenophorin, from which the absolute configuration of conglobatin has been inferred. The dimer consists of two molecules of 7-hydroxy-8-oxazoyl-2,4,6-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 8 publications
2
43
0
Order By: Relevance
“…FW-04-806, extracted from the China-native Streptomyces FIM-04-806 [14], is identical in structure to Conglobatin [15] according to ultraviolet spectra, infrared spectra, and NMR ( 1 H and 13 C) data and single-crystal X-ray diffraction data [16]. Cell proliferation assays have shown that FW-04-806 inhibits the growth of a human chronic myelocytic leukemia K562 cell line with an IC 50 of 6.66 μg/mL (almost 10 μM) [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FW-04-806, extracted from the China-native Streptomyces FIM-04-806 [14], is identical in structure to Conglobatin [15] according to ultraviolet spectra, infrared spectra, and NMR ( 1 H and 13 C) data and single-crystal X-ray diffraction data [16]. Cell proliferation assays have shown that FW-04-806 inhibits the growth of a human chronic myelocytic leukemia K562 cell line with an IC 50 of 6.66 μg/mL (almost 10 μM) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cell proliferation assays have shown that FW-04-806 inhibits the growth of a human chronic myelocytic leukemia K562 cell line with an IC 50 of 6.66 μg/mL (almost 10 μM) [16]. Conglobatin has been reported to be non-toxic at doses up to 1 g/kg when administered to mice either orally or interperitoneally [15]. In addition, our acute toxicity test showed that mice survived after oral administration of 900 mg/kg of FW-04-806.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Our ongoing studies have led to the discovery of two novel NFAT-133 analogs, panowamycins A (1) and B (2) isolated from a culture broth of Streptomyces sp. K07-0010, along with NFAT-133 (3), 6 conglobatin (4), 7 piericidins C 1 -C 4 (5-8) 8 and dinactin (11) 9 ( Figure 1). In this paper, the taxonomy of the producing strain, fermentation, isolation, physicochemical properties and structure elucidation of 1 and 2, and antitrypanosomal activities of isolated compounds are described.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas vermiculin exhibits an exocyclic ketopropyl side chain, an oxazole side chain is to be found in conglobatin, 11 isolated from Streptomyces conglobatus. However, 16-membered dilactones of the helmidiol type are found in pyrenophorin 9 isolated from the phytopathogen fungus Pyrenophora avenae and vermiculin 10 from Penicillium vermiculatum, which bears a keto group at C-4 (1: OH-4).…”
mentioning
confidence: 99%